A longitudinal 6-year study of the molecular epidemiology of clinical campylobacter isolates in Oxfordshire, United kingdom. - Cody, A; McCarthy, N; Wimalarathna, H; Colles, F; Clark, L; Bowler, I; Maiden, M; Dingle, K (2012)
Temporal and seasonal trends in Campylobacter genotypes causing human gastroenteritis were investigated in a 6-year study of 3,300 recent isolates from Oxfordshire, United Kingdom. Genotypes (sequence types [ST]) were defined using multilocus sequence typing and assigned to a clonal complex (a cluster of related strains that share four or more identical alleles with a previously defined central genotype). A previously undescribed clonal complex (ST-464) was identified which, together with ST-42, ST-45, and ST-52 complexes, showed increasing incidence. Concurrently, the incidence of ST-574, ST-607, and ST-658 complexes declined. The relative frequencies of three clonal complexes (ST-45, ST-283, and ST-42) peaked during summer and those of two (ST-353 and ST-403) peaked during winter. Nine clonal complexes (ST-22, ST-45, ST-48, ST-61, ST-257, ST-283, ST-403, ST-658, and ST-677) were significantly associated with ciprofloxacin sensitivity (P < 0.05). Seven clonal complexes (ST-49, ST-206, ST-354, ST-446, ST-460, ST-464, and ST-607) were associated with ciprofloxacin resistance (P < 0.05). Clonal complexes exhibited changing incidence and differences in seasonality and antibiotic resistance phenotype. These data also demonstrated that detailed surveillance at a single site captures information which reflects that observed nationally.